Policing China: street-level cops in the shadow of protest - Scoggins, Suzanne E. (Studies of the Weatherhead East Asian Institute, Columbia University, 2021)
"Evaluates the police bureaucracy in modern day China using interview and archival sources. Argues that despite projecting the appearance of a strong security state, the police bureaucracy in China is weak and plagued by problems of resources, enforcement, and oversight in virtually every area of policing except protest response"--